2022
DOI: 10.3390/magnetochemistry8050052
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Biologically Active Functionalized Azoles: NMR Spectroscopy and Quantum Chemistry

Abstract: This review summarizes the data on the stereochemical structure of functionalized azoles (pyrazoles, imidazoles, triazoles, thiazoles, and benzazoles) and related compounds obtained by multipulse and multinuclear 1H, 13C, 15N NMR spectroscopy and quantum chemistry. The stereochemistry of functionalized azoles is a challenging topic of theoretical research, as the correct interpretation of their chemical behavior and biological activity depends on understanding the factors that determine the stereochemical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 131 publications
0
7
0
Order By: Relevance
“…Since the tautomeric system is in a state of dynamic equilibrium, the stereochemical study of triazoles of this type is further complicated by the fact that for their prototropic states, it is extremely difficult (or impossible) to detect a 15 N NMR signal. Prototropic tautomerism of azoles, and in particular 1,2,3-triazoles, is a fairly fast process on the NMR time scale. ,, In the 1 H NMR spectra of the studied 1,2,3-triazoles, broad signals of the protons of the NH and OH groups are observed in the region of 14–16 and 11–12 ppm, respectively, see Table . Signals of carbon atoms in the 13 C NMR spectra are also broadened, thus, indicating the presence of an exchange tautomeric process.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Since the tautomeric system is in a state of dynamic equilibrium, the stereochemical study of triazoles of this type is further complicated by the fact that for their prototropic states, it is extremely difficult (or impossible) to detect a 15 N NMR signal. Prototropic tautomerism of azoles, and in particular 1,2,3-triazoles, is a fairly fast process on the NMR time scale. ,, In the 1 H NMR spectra of the studied 1,2,3-triazoles, broad signals of the protons of the NH and OH groups are observed in the region of 14–16 and 11–12 ppm, respectively, see Table . Signals of carbon atoms in the 13 C NMR spectra are also broadened, thus, indicating the presence of an exchange tautomeric process.…”
Section: Resultsmentioning
confidence: 96%
“…In light of the above, it should be noted that theoretical calculation of NMR chemical shifts is a powerful tool for determining the structure of organic molecules, natural products, and other biochemicals. Continuing our recent reviews of biologically active azoles, , the present study focuses on a series of functionalized 1,2,3-triazoles, which are shown in Scheme . A preliminary report regarding a conformational study of the first representative of this series was published in the Structural Chemistry .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the heterocyclic C(3) atoms for Et-TZ-PEG35 are observed at 147.68-147.75 ppm (5 in Figure 7), whereas the analogous carbon signal for the starting Et-NTZ is at 149.54 ppm (1 for Et-NTZ). The C(5) signal associated with the nitro group is poorly visible in the spectrum near 152.50 ppm (2 for Et-NTZ) for the substrate because of the quadrupolar broadening observed typical of azole nitro derivatives [37]. After the NO 2 group was substituted, the C(5) atoms of the terminal triazole rings related to the oligoether matrix are recorded at 148.69 ppm (6 in Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorus signal of PCl − 6 in the 31 P NMR spectra of compounds 73 and 75 appears in the region of −297.2 and −298.9 ppm, respectively. The large value of the direct coupling constant 1 J CH =180.0-187.0 Hz may indicate the influence of the lone electron pair (LEP) of the oxygen atom on the C-H bond, and in addition, the proximity of the carbon atom to the electronegative phosphorus (or nitrogen) atom in the cycle [50][51][52][53]. NQR spectroscopy data also indicate the formation of heterocyclic compounds.…”
Section: The Structure Of Enamide-derived Azaphosphorinesmentioning
confidence: 99%